Synthesis of Dihydroartemisinin using Ni/TiO2 catalyst Prepared by Sol Gel Method - Leonardus B.S. Kardono , , T. Wikara , , Harmita and S. Tursiloadi (Journal of Applied Pharmaceutical Science, 2014)
Artemisinin is a δ-sesquiterpene lactone that incorporates an endoperoxide moiety. This compound was isolated as the active compound of Artemisia annua L. Dihydroartemisinin is the simplest semisynthetic derivative of artemisinin and is more potent than artemisinin. Combined with piperaquine, curently this compound is the drug of choice to treat malaria. The objective of this research is to modify the structure of artemisinin into dihydroartemisinin. A new way to modify the structure of artemisinin into dihydroartemisinin, had been successfully conducted using hydrogenation process with Ni/TiO2 catalyst. The yield of the reaction was 16.58%. LC-MS analysis showed that the compound had mainly a peak with retention time tR 2.2 minutes and mass spectrum showed that the molecular weight of the compound was 284.29 which was the molecular formula of dihydroartemisinin, C15H24O5. The IR spectrum showed that there was a spectrum from C-O in a wave number of 1034.14 cm-1. Hydrogenation reaction did not destroy the endoperoxide group. This was proven by the existing of C-O-O-C in a frequency of 1091.71; 875.68; 844.82 cm-1. 1H- and 13C-NMR data and comparison to the authentic sample, showed that the compound was a racemic mixture of α/β dihydroartemisinin. The dihydroartemisinin resulted from this process was also proven for its antimalarial activity, in vitro assay using cultured Plasmodium falciparum clone 3D7 with its IC50= 2x10-7M.
Keywords: Dihydroartemisinin, Synthesis, Hydrogenation, Ni/TiO2 catalyst, sol gel.